Construction and validation of a logical model for specialized Rehabilitation Centers - Valentim, Regis de Souza; Dantas, Thaissa Hamana de Macedo; Machado, Flavia Christiane de Azevedo; Araújo, Camilla Medeiros; Silva, Marilene Soares da; Castaneda, Luciana; Dantas, Diego (Revista de Saúde Pública, 2021)
OBJECTIVE To build and validate a logical model for health care in Specialized Rehabilitation Centers (CER) by analyzing the work process and organizational issues of centers in Rio Grande do Norte. METHODS This is a methodological study developed in three stages: 1) documentary research of legislation and ordinances concerning the healthcare service and the Disability Care Network (RCPD); 2) focus groups with a Census study of the CER in Rio Grande do Norte to understand and assess the daily activities of the service; and 3) systematization of the information collected and, finally, proposition and validation of the evaluative logical model. RESULTS The model encompassed five central categories of the work and organizational process: “demands”, “resources” (inputs, financial and workforce), “processes”, “products and results” and “mission, values and external factors”. CONCLUSION The logical model built was suitable for graphical representation of the work process and organizational issues of the SRC. The study showed that the functioning of the services is in line with the regulations. However, there are still organizational gaps that need to be addressed to improve the resolution capacity of the service and the articulation with other points of the network.